2014
DOI: 10.5539/elt.v7n11p15
|View full text |Cite
|
Sign up to set email alerts
|

Generic Reference in English, Arabic and Malay: A Cross Linguistic Typology and Comparison

Abstract: According to the Longman Grammar of Spoken and Written English 1999 by Biber et al. (p. 266) generic article uses are more than twice as common in academic English than in conversation or fiction. This is an area that English for Academic Purpose (EPA) textbooks and teachers would need to target more than general English teaching. This paper is therefore a contribution towards better understanding of what linguistic facts about generics teachers and textbooks of EAP might need to cover in order to deal with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Semantic countability is expressed by the definiteness system in English, but not in PA. PA and English definiteness systems interfere with Arabic native speakers' acquisition of English as a second language (Harb, 2014;Husni and Newman, 2015). There is strong evidence of the effects of Arabic countability properties in their errors (in which countability significantly interferes with abstractness as well) (Aboras 2020;Alenizi 2013Alenizi , 2017Al-Malki et al 2014;Naim-Bader 1988). Arabic learners of English overuse the definite article in idioms, with abstract and uncountable nouns, and in generic plural noun phrases: (7) *the value of the time (8) *he sell the apples at the crossroad (9) * the milk is nutritious to the body (10) *I went to the bed (11) *you cook the rice (12) *the horses are useful animals.…”
Section: Linguistic Definiteness Semantic Countability and Cognitive ...mentioning
confidence: 99%
“…Semantic countability is expressed by the definiteness system in English, but not in PA. PA and English definiteness systems interfere with Arabic native speakers' acquisition of English as a second language (Harb, 2014;Husni and Newman, 2015). There is strong evidence of the effects of Arabic countability properties in their errors (in which countability significantly interferes with abstractness as well) (Aboras 2020;Alenizi 2013Alenizi , 2017Al-Malki et al 2014;Naim-Bader 1988). Arabic learners of English overuse the definite article in idioms, with abstract and uncountable nouns, and in generic plural noun phrases: (7) *the value of the time (8) *he sell the apples at the crossroad (9) * the milk is nutritious to the body (10) *I went to the bed (11) *you cook the rice (12) *the horses are useful animals.…”
Section: Linguistic Definiteness Semantic Countability and Cognitive ...mentioning
confidence: 99%
“…The outstanding contributors to the study of generic reference are (e.g. Wijaya, 2012;AL-Malki et al, 2014;Tomás, 2016). Wijaya's study is titled Teaching English Generic Nouns: The Exploration of The Generic Idea in English and Indonesian and The Applications of Explicit Instruction in Classroom.…”
Section: Review Of Previous Studies On Generic Referencementioning
confidence: 99%
“…Arabic speakers with different dialects commonly drop the indefinite article. Al-Malki, Majid, and Mohd Omar (2014) found that most Arabic dialects tend to drop the indefinite article (nunnation), except in the cases of a few Bedouin dialects. Saudi Arabic speakers tend to drop the indefinite and the absence of the definite article (al-) by using bare nouns to indicate the indefinite context in Saudi Arabic.…”
Section: Feature Differences Between Arabic and Englishmentioning
confidence: 99%